a) Để M thuộc Z <=> \(x+2\in B\left(3\right)=\left\{0;3;-3;6;-6;....\right\}\)
<=> x = B(3) - 2
b) Để N thuộc Z <=> 7 chia hết cho x-1
<=> \(x-1\inƯ\left(7\right)=\left\{1;7;-1;-7\right\}\)
Nếu x - 2= 1 thì x = 3
Nếu x - 2 = -1 thì x = 1
Nếu x - 2 = 7 thì x = 9
Nếu x - 2 = -7 thì x = -5
Vậy x = {-5;1;3;9}
a) Để M thuộc Z <=> x+2∈B(3)={0;3;−3;6;−6;....}
<=> x = B(3) - 2
b) Để N thuộc Z <=> 7 chia hết cho x-1
<=> x−1∈Ư(7)={1;7;−1;−7}
Nếu x - 2= 1 thì x = 3
Nếu x - 2 = -1 thì x = 1
Nếu x - 2 = 7 thì x = 9
Nếu x - 2 = -7 thì x = -5
Vậy x = {-5;1;3;9}
a ) M = x + 2 / 3 \(\in Z\)
=> x + 2 \(⋮3\)( hay x + 2 là bội của 3 )
=> x + 2 \(\in\left\{...;-9;-6;-3;0;3;6;9;12;...\right\}\)
=> x \(\in\left\{...;-11;-8;-5;-2;1;4;7;10;...\right\}\)
b ) \(N=\frac{7}{x-1}\in Z\)
=> 7 \(⋮\left(x-1\right)\)( hay x - 1 là ước của 7 )
=> x - 1 \(\in\left\{-7;-1;1;7\right\}\)
=> x \(\in\left\{-6;0;2;8\right\}\)